Intermittent preventive treatment with dihydroartemisinin–piperaquine and risk of malaria following cessation in young Ugandan children: a double-blind, randomised, controlled trial. Issue 9 (September 2019) - Muhindo, Mary K; Jagannathan, Prasanna; Kakuru, Abel; Opira, Bishop; Olwoch, Peter; Okiring, Jaffer; Nalugo, Noeline; Clark, Tamara D; Ruel, Theodore; Charlebois, Edwin; Feeney, Margaret E; Havlir, Diane V; et al.
Summary: Background: Intermittent preventive treatment (IPT) of malaria with dihydroartemisinin–piperaquine is a promising strategy for malaria prevention in young African children. However, the optimal dosing strategy is unclear and conflicting evidence exists regarding the risk of malaria after cessation of chemoprevention. We aimed to compare two dosing strategies of IPT with dihydroartemisinin–piperaquine in young Ugandan children, and to evaluate the risk of malaria after cessation of IPT. Methods: In this double-blind, randomised controlled phase 2 trial, women and their unborn children were recruited at Tororo District Hospital (Tororo, Uganda). Eligible participants were HIV-negative women aged 16 years or older with a viable pregnancy (gestational age 12–20 weeks). Women and their unborn children were randomly assigned (1:1:1:1) to one of four treatment groups, all receiving dihydroartemisinin–piperaquine, on the basis of the IPT intervention received by the woman during pregnancy: women every 8 weeks, children every 4 weeks; women every 4 weeks, children every 4 weeks; women every 8 weeks, children every 12 weeks; and women every 4 weeks, children every 12 weeks. Block randomisation was done by an independent investigator using a computer-generated randomisation list (permuted block sizes of six and 12). We analysed children on the basis of their random assignment to receive dihydroartemisinin–piperaquine (20 mg/160 mg tablets) once daily for 3 consecutive days every 4 weeks or 12 weeks. Children received study drugs from age 8 weeks to 24 months and were followed-up to age 36 months. Participants and investigators were masked to treatment allocation. The primary outcome was the incidence of symptomatic malaria during the intervention and following cessation of the intervention, adjusted for potential confounders. The primary outcome and safety were assessed in the modified intention-to-treat population, which included all children who reached 8 weeks of age and received at least one dose of study drug. This trial is registered with ClinicalTrials.gov, number NCT02163447 . Findings: Between Oct 21, 2014, and May 18, 2015, 191 children were born, of whom 183 reached 8 weeks of age and received at least one dose of study drug and thus were included in the primary analysis (96 children in the 4-week group and 87 in the 12-week group). During the intervention, the incidence of symptomatic malaria was significantly lower among children treated every 4 weeks than children treated every 12 weeks; three episodes occurred among children treated every 4 weeks (incidence 0·018 episodes per person-year) compared with 61 episodes among children treated every 12 weeks (incidence 0·39 episodes per person-year; adjusted incidence rate ratio [aIRR] 0·041, 95% CI 0·012–0·150, p<0·0001). After cessation of IPT, children who had previously received dihydroartemisinin–piperaquine every 4 weeks had a lower incidence of symptomatic malaria than children who were treated every 12 weeks; 62 episodes occurred among children previously treated every 4 weeks (incidence 0·73 episodes per person-year) compared with 83 episodes among children treated every 12 weeks (incidence 1·1 episodes per person-year; aIRR 0·62, 0·40–0·95, p=0·028). In the 4-week group, 94 (98%) of 96 children had adverse events versus 87 (100%) of 87 children in the 12-week group. The most commonly reported adverse event was cough in both treatment groups (94 [98%] in the 4-week group vs 87 [100%] in the 12-week group). 16 children had severe adverse events (seven [7%] children in the 4-week group vs nine [10%] children in the 12-week group). No severe adverse events were thought to be related to study drug administration. One death occurred during the intervention (age 8 weeks to 24 months), which was due to respiratory failure unrelated to malaria. Interpretation: IPT with dihydroartemisinin–piperaquine given every 4 weeks was superior to treatment every 12 weeks for the prevention of malaria during childhood, and this protection was extended for up to 1 year after cessation of IPT. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development.